Body posture and academic performance of fifth-year students at a school in Chiclayo 2024 - Edgard, Davila Bravo, Harrinson; Nicoly, Delgado Torres, Danna; Analith, Tafur Barboza, Tatiana; Joel, Viera Ramos, Fabián; Margot, Segura Saldarriaga, Adriana (Edelweiss Applied Science and Technology, 2025)
The study aligned with the Sustainable Development Goal (SDG) 3, related to health and well-being, and aimed to analyze the relationship between body posture and the academic performance of fifth-year high school students in Chiclayo. It was a basic research study with a quantitative approach and a non-experimental cross-sectional design. The sample consisted of 90 students selected using a formula for finite populations, employing a questionnaire of 15 questions per variable as a data collection instrument. The results showed a significant correlation between body posture and academic performance, with sufficient evidence to assert that improvements in posture could be associated with better school performance. Therefore, this finding fulfilled the general objective of the study, emphasizing the importance of posture in academic performance. In conclusion, it was recommended to implement educational programs focused on correcting and improving students’ body posture, highlighting its positive impact on both learning and overall well-being.